PERBANDINGAN UNSUR HARA PADA KOMPOS PELET SISA PAKAN SAPI DENGAN BAHAN AKTIF BETA DAN ECO FARMING - Agus Susanto Ginting; Sumatera Tarigan (JURNAL AGROTEKNOSAINS, 2022)
Active ingredients or also known as activators have an important role in  decomposition process of materials during composting. The active ingredient acts as a catalyst that breaks down the lignocellulose contained in the main ingredients of compost into simpler chain. In this research, the active ingredients used in the composting process are Beta and Eco Farming. The advantages of these two active ingredients in addition to acting as active ingredients are also rich in nutrients needed by plants. The nutrients produced from this decomposition process will be compared with the established standard, namely the Indonesian National Standard (SNI) 19-7030-2004. The results of the analysis showed that the macronutrient content of the two active ingredients in the pellet compost product made from cow feed was in accordance with the standards set with the values of nitrogen (>0.4%), phosphorus (>0.1), and potassium (>0, 2). the c-organic content is in the standard range that has been set (9.8%-32%). The percentage of water content is below the maximum water content that has been set (50%). The acidity level (pH) for pellet compost with Beta active ingredients is in the standard lifting range with value of 7.17 while pellet compost with Eco Farming active ingredients has a pH of 7.88 which is close to the maximum standard value of 7.48. The number of C/N ratio is still higher than the standard set so that it takes a longer time in the fermentation process so that the appropriate number is obtained.